2015
DOI: 10.4238/2015.october.18.56
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequence characterization, and expression patterns of members of the porcine TSSK family

Abstract: ABSTRACT. Testis-specific serine kinases (TSSKs) are a family of serine/ threonine kinases highly expressed in the testes that are responsible for regulating many spermatogenesis-related protein activities. Mutations in this family have a positive relationship with oligospermia and azoospermia in human and mouse. Here, five members of the TSSK family from a Banna mini-pig inbred line (BMI) were cloned, sequenced, and characterized. The (2015) full-length coding sequences of BMI TSSKs varied from 807 (TSSK3) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In present study, five Tssk genes were identified in the scallop A. irradians, which is comparable with that of vertebrates (six in mouse and five in human and porcine; Li et al, 2011;Wang et al, 2015a). It suggests no significant duplication events occurred for Tssk family during the evolution of bilateria.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In present study, five Tssk genes were identified in the scallop A. irradians, which is comparable with that of vertebrates (six in mouse and five in human and porcine; Li et al, 2011;Wang et al, 2015a). It suggests no significant duplication events occurred for Tssk family during the evolution of bilateria.…”
Section: Discussionsupporting
confidence: 70%
“…In recent years, a family of testis-specific protein kinases, called as testis-specific serine/threonine kinases (Tssks), has attracted researcher's interest due to their essential roles in spermatogenesis (Wang et al, 2015a;Li et al, 2016;Kim et al, 2019). Six Tssk subfamilies have been reported in mammals, including Tssk1 through Tssk6, which have the conserved serine/ threonine protein kinases catalytic (S_TKc) domain (Wang et al, 2015a). Most of them are specifically expressed in spermatids or sperm (Li et al, 2011) and have been demonstrated to play essential roles in spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the RT-PCR-based tissue expression assay, abalone TSSK1-like displayed a testis-predominant pattern of mRNA expression, which is typically observed in mammalian TSSK1 [4,42]. Furthermore, expression levels of abalone TSSK1-like transcripts were readily affected by both age and reproductive cycles of the males, in which there was a positive relationship between TSSK1-like expression levels and the degree of testis maturation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] reported that three TSSK orthologs are expressed in the nematode Caenorhabditis elegans and that deletion mutants carry male gametes with different degrees of abnormality. In 2015, five members of the TSSK family were cloned and characterized in a Banna mini-pig inbred line [ 37 ]. Very recently, a TSSK1-like gene was cloned and characterized in the Pacific abalone species, Haliotis discus hannai [ 38 ], a commercially important marine gastropod.…”
Section: Discovery and Cloning Of Tssksmentioning
confidence: 99%